2006
DOI: 10.1016/j.immuni.2006.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Human NK Cell Education by Inhibitory Receptors for MHC Class I

Abstract: Natural killer (NK) cells recognize the absence of self MHC class I as a way to discriminate normal cells from cells in distress. In humans, this "missing self" recognition is ensured by inhibitory receptors such as KIR, which dampen NK cell activation upon interaction with their MHC class I ligands. We show here that NK cells lacking inhibitory KIR for self MHC class I molecules are present in human peripheral blood. These cells harbor a mature NK cell phenotype but are hyporesponsive to various stimuli, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

53
1,027
2
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,022 publications
(1,108 citation statements)
references
References 41 publications
(76 reference statements)
53
1,027
2
9
Order By: Relevance
“…Several in vivo data provided a hint that hyporesponsive NK cells that do not express inhibitory receptors can still function during infectious diseases [4,8]. Besides, it has been controversially discussed whether IL-2 stimulation could reverse NK-cell hyporesponsiveness [5,10]. In our system, only acquisition of self-MHC-specific KIR (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several in vivo data provided a hint that hyporesponsive NK cells that do not express inhibitory receptors can still function during infectious diseases [4,8]. Besides, it has been controversially discussed whether IL-2 stimulation could reverse NK-cell hyporesponsiveness [5,10]. In our system, only acquisition of self-MHC-specific KIR (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…2). Our findings support the concept that, once a KIR is acquired, even after in vitro cytokine stimulation, its expression remains stable.Acquisition of self-specific KIR confers functional competence an CD56 dim KIR À NKG2A -NK cells Since ex vivo expression of self-specific inhibitory receptors correlates with NK-cell functional competence [5,6], we wanted to evaluate whether acquisition of KIR expression after cytokine stimulation confers competence on CD56 dim KIR À NKG2A À hyporesponsive NK cells and whether engagement of self-MHC is required. To answer these questions, KIR3DL1 expression was induced in CD56 dim KIR À NKG2A À NK cells from HLA-Bw4 or HLA-Bw6 individuals that do or do not express the cognate MHC ligand for KIR3DL1, respectively.…”
mentioning
confidence: 99%
“…These features, together with high expression of cytolytic molecules, allow CD56 dim NK cells to efficiently lyse target cells either directly or indirectly through CD16‐mediated antibody‐dependent cellular cytotoxicity (ADCC). The expression of a family of receptors called killer immunoglobulin‐like receptors (KIRs), which modulate the responsiveness of NK cells to activating receptor ligation,62, 63 is also restricted to CD56 dim NK cells.…”
Section: Subsets Of Nk Cellsmentioning
confidence: 99%
“…At the immature DX5 -stage, NK cells express multiple NK receptors including CD94/NKG2, NKG2D and NKp46, but are unable to perform granule-mediated cytotoxicity [21][22][23]. During maturation to DX5 + mature cells, NK cells start to express Ly49 MHC class I receptors [22][23][24], and undergo an education process during which NK cells expressing inhibitory receptors that recognize self MHC class I are "licensed" to perform more potent effector functions [25][26][27][28].cd T cells, like ab T cells, develop in the thymus, where V(D)J recombination of TCR genes occurs. Using T cell receptor d locus-histone 2B-enhanced GFP (Tcrd-H2BEGFP) knock-in mice in which an IRES-controlled H2B-EGFP fusion protein is present in the 3 0 untranslated region of the Tcrd constant gene [29], we have recently shown that developing cd T cells undergo a "TCR quality control checkpoint" upon successful expression of TCRcd.…”
mentioning
confidence: 99%